A Model for Resolving Bullying Cases Against Children in Muara Village, Cirebon Regency That is Fair - Wahyunda, Putri; Sarah, Sarah; Sanusi , Sanusi; Hendra , Raden (PT FORMOSA CENDEKIA GLOBAL, 2025)
Bullying of children is a social problem that is getting more and more attention, especially in rural environments where there are limitations in the child protection system. This study aims to examine the model of resolving bullying cases against children in villages in Cirebon regency with a fair approach, both in formal law and local wisdom. The method used is qualitative with data collection techniques through interviews, observations, and documentation studies of several parties, such as village officials, community leaders, victims, perpetrators, and child protection institutions. Bullying perpetrators are also at risk of experiencing mental health disorders, such as uncontrolled emotional symptoms. On the other hand, children who are victims of bullying will suffer as a result of physical and non-physical violence. One of the steps that can be taken to help perpetrators or victims of bullying is to give more affection, rebuild confidence, and involve them in various positive activities. It is essential to provide an understanding of the adverse effects of bullying. The results of this study show that the fair settlement model combines for restorative mediation, the involvement of indigenous leaders, as well as education and recovery of victim trauma, and the resolution of repeated bullying cases. This study recommends the need for integrity between the state legal system and local values in handling cases of bullying against children.